High levels of serum matrix metalloproteinases in dogs with natural visceral leishmaniosis: A preliminary report - Melo, Guilherme D.; Marangoni, Natalia R.; Marcondes, Mary [UNESP]; Lima, Valeria M. F. [UNESP]; Machado, Gisele Fabrino [UNESP] (Elsevier B.V., 2011)
The hallmark microscopic lesion in canine visceral leishmaniosis is the accumulation of lymphocytes and macrophages parasitized by amastigotes of Leishmania in the lymphoid organs. Matrix metalloproteinase (MMP)-2 and MMP-9 are important for leukocyte migration as they degrade the type IV collagen in the basal lamina. Sera from 65 dogs, 53 with serological diagnosis of visceral leishmaniosis and 12 healthy ones, were analysed by gelatin-zymography to detect MMP-2 and MMP-9 activity. The infected dogs presented higher levels of serum mature MMP-9, proMMP-9 and proMMP-2 than control dogs. No mature MMP-2 activity was observed. The levels of mature and proMMP-9 were highly correlated. These findings suggest that the multi-systemic inflammatory lesions observed in visceral leishmaniosis are associated with an increase in serum MMPs, especially MMP-9. In concert with other clinical data, quantification of serum MMP-9 in infected dogs may lead to a better understanding of the pathogenesis of visceral leishmaniosis. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cellular migration; Leishmania chagasi; MMP-2; MMP-9; Serum marker; Zymography